EVALUASI SISTEM INFORMASI AKUTANSI PEMBELIAN DAN PENJUALAN PADA TOKO BAJU MAYANG STORE DI BONDOWOSO - Santoso, Dimas Rizki Dwi; Halim, Moh.; Aspirandi, Rendy Mirwan (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Information system sales and purchases of goods is a system that provides information services in the form of transaction data sales and purchases of goods. The existence of this information system is important. in this case the Mayang Store is used as a place of research, because the shop still does not use an accounting information system, resulting in errors in existing reports, such as processing sales data and purchasing data. The purpose of this study is to provide convenience when processing sales and purchase transaction data. This research resulted in several uses consisting of practical and academic uses. The type of research used by researchers is qualitative research and the types of data used are primary data and secondary data. This information system was built in order to provide convenience in processing sales and purchase data, as well as processing sales and purchase reports more accurately.